Pengaruh Abdominal Stretching Exercise terhadap Intensitas Nyeri pada Siswi Kelas XI yang Mengalami Dismenore di SMK Negeri 3 Raha Kecamatan Batalaiworu Kabupaten Muna - Purnawati, Fantri; Said, Asbath (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2017)
Abdominal Stretching Exercise is one of the non-pharmacological therapies in the treatment of dysmenorrhea in adolescents, which can interfere with learning activities and indirectly affect the productivity and quality of life of adolescents. The incidence of dysmenorrhea in Indonesia is 64.25%. Based on the researcher's initial survey with 20 respondents at SMKN 3 Raha, 6 of them experienced dysmenorrhea in the mild pain category, 7 people experienced moderate pain, 1 person experienced severe pain, and 6 people did not experience pain during menstruation. The purpose of this study was to determine the effect of Abdominal Stretching Exercise on pain intensity in class XI students who experienced dysmenorrhea at SMKN 3 Raha, Batalaiworu sub-district, Muna district in 2016. This type of research is pre-experimental with a one-group pretest-posttest design. The population in this study was 75 people, with the technique of sampling by accidental sampling, with a total sample of 19 people. The method of analysis used the Paired sample t-test statistical test. The results showed that there was a significant effect of Abdominal Stretching Exercise on the intensity of pain in female students who experienced dysmenorrhea. This can be seen from the value of the Statistical Test (p = 0.000) < (0.05), which shows a significant difference. It is hoped that nurses will continue to socialize the provision of Abdominal Stretching Exercise in reducing pain during menstruation which is felt by women as an independent nurse action.